Preliminary model development for archipelago country logistic system - Rafi, Salahudin (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
Indonesia, the largest island country in the world, requires a reliable logistics system to meet its people's needs. The National Logistics System Development Blueprint (SISLOGNAS) supports this process, increasing trade, economic productivity, infrastructure investment, and employment opportunities. However, Indonesia's logistics performance index is currently ranked 61st out of 139 countries surveyed. To address these issues, an initial model was developed for national logistics system variables for archipelagic countries. This research uses an exploratory factor analysis approach with Jamovi software. The study found that 50 indicators in the logistics system of an archipelagic country like Indonesia are classified into six categories: services, commodities, logistics infrastructure, modes of transportation, timeliness, and technology. These indicators interconnect to develop an effective and efficient national logistics network